How to measure transfer of training in Higher Education: the questionnaire of transfer factors - Mònica Feixas Condom; María del Mar Duran; Idoia Fernández Fernández; Amparo Fernández; María José Garcia San Pedro; María Dolors Márquez; Pilar Pineda; Carla Quesada; Sarai Sabaté Díaz; Marina Tomàs-Folch; Franziska Zellweger; Patricio Lagos (Universitat Politècnica de València, 2013)
This article aims to present the main outcomes of a research about the factors influencing the transfer potential of university teachers' training into the daily practice. Based on a previous study (Feixas and Zellweger, 2010), a Questionnaire on Factors Conditioning Learning Transfer of Teacher's Training has been designed and applied to participants of academic development activities of Spanish universities. Additionally, an analysis of the training activities of Spanish universities and three focus groups with experts, trainers and participants have been conducted. The application of the instrument to 18 universities (n=1.026) and the corresponding exploratory factor analysis allowed us to examine the model's construct validity (Cronbach's alpha: .91) and have resulted in the emergence of eight factors that affect learning transfer: factors related to the training design (training design and learning achieved), environmental factors (support of the study program's coordinator, readiness to change, environment resources, student feedback , institutional recognition, teaching culture of the teachers' team) and individual factor (personal organization of the work). The analysis of the training designs informs us of a trend predominantly technical and prescriptive which is conceived for the punctual development of skills.